(untitled) (World Bulletin of Public Health, 2024)
This scientific article examines some features of the normal morphology of the rectum in white outbred rats. The purpose of the study was to study the anatomical and structural characteristics of the rectum in non-breed rats to gain a more complete understanding of its functions and possible abnormalities. The technique included anatomical and histological analysis of the rectum in 50 white outbred rats. Parameters such as length, diameter and structure of the walls of the rectum were studied. The results were also compared with data from previous studies on this topic. The study results showed that the rectum in outbred albino rats has similar anatomical and structural characteristics to the rectum in other rat species. However, some differences have been identified in the length and diameter of the rectum in outbred albino rats compared to other species.